Estudio de la biodiversidad acuática de vertebrados en la Amazonía y Orinoquía colombiana por medio de ADN ambiental (2021)
The massive loss of biodiversity in recent years has driven the development of rapid, cost-effective, non-invasive, and efficient sampling alternatives, such as environmental DNA. With this method, a water sample can evaluate a community's diversity, and low abundance, cryptic, and threatened species can also be detected. In this study, environmental DNA was used to determine the diversity of aquatic vertebrates in the Bojonawi Natural Reserve (RNB) and adjacent areas, the Sierra de la Macarena National Natural Park, Puerto Nariño, and adjacent areas, and the Municipality of Solano. In locations distributed in the Colombian Amazonas and Orinoquia regions. A total of 728 OTUs were identified for all localities. The Orinoco river presents the highest number of fish genera (67), and the Guayabero river, the largest number of genera for other vertebrates (13). New records were taken on all locations, including the Oilbird (Steatornis caripensis) and the Peale's free-tailed bat (Nyctinomops aurispinosus)...